Equilibrium and Thermodynamic Studies of Removal of Two Dyes from Aqueous Solutions using Low Cost Adsorbent - Hussain, Zainab (Al-Nahrain Journal of Science, 2018)
The capability of the low cost materials viz. Dried Mint Leaves (DML) to eliminate two cationic dyes, Methylene Blue (MB) and Safranin-O (SF-O) from an aquatic solutions was studied by the technique of batch mode adsorption process. Influence of contact time, initial dye concentration (mg/L), adsorbent amount (g/L) and temperature was investigated. The equilibrium and thermodynamic peculiarities of the dyes abscession were too inspected. The empirical data were found to comply the Langmuir and Freundlich models. Also Dubinin-Radushkevich model show that the process was physisorption. The negative free energy pointed to that the adsorption processes were spontaneously feasible. The process of adsorption has been existed to be exothermic in nature. The abscession of MB was found to be more spontaneous and feasible than the removal of SF-O on the adsorbent.